2019
DOI: 10.7717/peerj.7237
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to predict the prognosis of parotid gland mucoepidermoid carcinoma: a population-based study of 1306 cases

Abstract: Background Mucoepidermoid carcinoma (MEC) is a common cancer in the oral salivary gland malignancy, which mainly occurs in the parotid gland. The aim of this study is to identify independent prognostic factors and establish a nomogram model for parotid gland mucoepidermoid carcinoma (P-MEC) patients using the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database. Method Patients with P-MEC were selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…The prognostic value of PRT has been explored in several studies, and it remains controversial, with some authors believing that PRT can significantly improve the prognosis of PGC patients, 23 others considering that PGC patients cannot benefit from PRT, 6,22 and some even thinking that PRT will impair survival due to its adverse effects 11,42 . The present study found no significant difference in the GCD risk between patients who received both surgery and radiotherapy and those who received only surgery.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The prognostic value of PRT has been explored in several studies, and it remains controversial, with some authors believing that PRT can significantly improve the prognosis of PGC patients, 23 others considering that PGC patients cannot benefit from PRT, 6,22 and some even thinking that PRT will impair survival due to its adverse effects 11,42 . The present study found no significant difference in the GCD risk between patients who received both surgery and radiotherapy and those who received only surgery.…”
Section: Discussioncontrasting
confidence: 55%
“…Patients with palpable lymphadenopathy are treated with radical or modified radical neck dissection 6 . And chemotherapy is mainly applied in the palliative setting 11 . The treatment strategy in individual patients is determined based on evaluations of the prognosis, 5,6,11‐14 and so inaccurate prognostic predictions may lead to either inadequate or excessive treatment 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 variables determined in this study, these predictors have been proven in other studies (20,21). Nine (age, AJCC stage, radiation, T stage, M stage, grade, surgery, N stage, and histological type) were established as indicators of CSD in persons with PC via univariate coupled with the Lasso Cox regression model competing risk assessment.…”
Section: Discussionmentioning
confidence: 88%
“…A nomogram is a visualization tool that has been widely used to predict the prognosis of cancer patients [4][5][6][7] . It is valuable for clinical decision-making and patient counseling.…”
Section: Introductionmentioning
confidence: 99%